A case of COVID-19 in pregnancy complicated by fetal pleural effusion - Natalia Filochowska; Łukasz Witek; Helena Sławska; Anita Olejek (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which can lead to severe respiratory failure, has become a real threat to pregnancy. Although vertical transmission of the virus through the placenta appears to be rare, there is increasing evidence that a SARS-CoV-2 infection may cause complications during pregnancy. We report a case of COVID-19 in a pregnancy complicated by fetal pleural effusion in the third trimester of pregnancy. To our knowledge, only 4 similar cases have been reported to date. A 29-year-old woman in the 37th week of pregnancy admitted to the department of pregnancy pathology due to right fetal pleural effusion. In the 34th week of pregnancy, the patient suffered from COVID-19 with symptoms of fever and general weakness. The infection was confirmed by reverse-transcription polymerase chain reaction (RT-PCR). At 38 weeks, vaginal delivery occurred. The male newborn with a 6/7/8 point Apgar score required continuous positive airway pressure (CPAP) breathing assistance and was transferred to the intensive care unit. The rapid antigen test was negative. The ultrasound showed collapse of the right lung compressed by fluid in the pleural cavity. Inflammation, congenital TORCH and group B Coxsackie virus infection, chromosomal disorders and anatomical defects were excluded. During hospitalization 850 ml of lymphatic fluid was drained. We suspect a possible causal relationship between non-immune fetal hydrops and coronavirus disease.